2012
DOI: 10.1007/s10765-012-1292-z
|View full text |Cite
|
Sign up to set email alerts
|

Lock-in and Heterodyne Carrierographic Imaging Characterization of Industrial Multicrystalline Silicon Solar Cells

Abstract: A novel non-destructive, non-contact laser-induced near-infrared imaging technique using an InGaAs camera and based on dynamic carrierography (a spectrally gated modulated photoluminescence modality) was used in direct lock-in (LICG) and heterodyne (HDCG) modes to characterize industrial multicrystalline silicon solar cells. The image amplitude depends on the free-photocarrier diffusion-wave density, the spatial resolution is a function of modulation frequency, and the contrast is due to the spatial distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Therefore, the value of γ can be used to physically interpret the linear or nonlinear behavior of a charge carrier recombination process with respect to the laser excitation and reveals the underlying radiative recombination process. It is an important parameter for the LIC process because nonlinear PL responses to the laser excitation, acting as a nonlinear frequency mixer, are essential for PL-based heterodyne LIC imaging. ,,, …”
Section: Theoretical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the value of γ can be used to physically interpret the linear or nonlinear behavior of a charge carrier recombination process with respect to the laser excitation and reveals the underlying radiative recombination process. It is an important parameter for the LIC process because nonlinear PL responses to the laser excitation, acting as a nonlinear frequency mixer, are essential for PL-based heterodyne LIC imaging. ,,, …”
Section: Theoretical Methodsmentioning
confidence: 99%
“…It is an important parameter for the LIC process because nonlinear PL responses to the laser excitation, acting as a nonlinear frequency mixer, are essential for PL-based heterodyne LIC imaging. 40,42,43,46 As opposed to CQD thin films, excitons in polycrystalline and amorphous Si wafers, upon their formation, immediately dissociate into free electrons and holes, with the dominant recombination process being via defect states. In this situation, the nonlinear recombination term an 2 in the rate equation…”
Section: Can Be Expressed Bymentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome the abovementioned limitations, a heterodyne scheme has been proposed . The idea is to construct a slow enough beat frequency component through frequency mixing.…”
Section: Introductionmentioning
confidence: 99%
“…The inspection of the entire solar cell area or some specific regions can also fulfill various other purposes such as overall device performance, shading effects, electrical, and/or mechanical defects. Solar cell large‐area imaging has been used intensively with perovskite solar cells using camera‐based photoluminescence, series resistance imaging using electroluminescence, lock‐in thermography (LIT), lock‐in carrierography (LIC) characterization of Si wafers, and solar cells . However, to the best of our knowledge, no imaging studies of CQDSCs have been reported in efforts to acquire an insightful physical picture of defect or contact effects on key solar cell performance parameters.…”
Section: Introductionmentioning
confidence: 99%